Coir Pith as Growth Medium for Azotobacter Vinelandii and Azospirillum Brasilense - Reghuvaran, Abesh; Ravindranath, Anita Das (International Coconut Community Journal, 2011)
Coir pith is a lignocellulosic biomass which is recalcitrant under ordinary conditions. Nitrogen fixation is commonly carried out in the soil and these soils acts as the medium for plant growth. This paper attempts to utilize coir pith as a substrate for two important nitrogen fixing organisms viz. Azotobacter vinelandii and Azospirillum brasilense. Coir pith was used as a source of carbon and energy by the bacteria and the ammonia produced during the process of nitrogen fixation was studied, the amount of ammonia produce indicates the fixation process by the bacteria. The present work succeeded in establishing the use of these two organisms to degrade the coir pith effectively and the resultant biodegraded material could be used as organic manure for plants.